Guanine derivatives as promising candidates for the development of purine-based antimalarial drugs - Tashie, Worlanyo; de Koning, Harry P.; Duah-Quashie, Nancy O.; Quashie, Neils B. (Frontiers in Parasitology, 2025)
IntroductionThe increasing resistance of Plasmodium falciparum to existing antimalarial drugs drives the urgent need for novel therapeutic strategies. The purine salvage pathway in P. falciparum is essential for the parasite’s survival due to its complete reliance on host-derived purines for nucleic acid synthesis and other essential processes. Although the purine salvage system has been intensively researched, no purine-based antimalarial drugs have been taken into preclinical development. The current study evaluated the chemotherapeutic potential of some purine nucleobase analogues against P. falciparum.MethodsIn vitro sensitivity assays were conducted using the 72-hour SYBR Green drug assay on laboratory-adapted P. falciparum strains 3D7 and Dd2. The most potent nucleobase analogues were docked into PfENT1 using the PyRx software suite.ResultsThe analogues 8-azaguanine, 7-deazaguanine, and 6-thioguanine exhibited average EC50 values of 1.71 µM, 14.9 µM and 15.7 µM, respectively, for 3D7 and 5.2 µM, 16.3 µM and 18.6 µM, respectively, for the Dd2 strain, and subsequently tested against field isolates of P. falciparum. These ex vivo tests showed EC50 values ranging from 0.5 - 4.5 µM for 8-azaguanine, 3.8 - 12.3 µM for 7-deazaguanine, and 4.1 - 15.0 µM for 6-thioguanine. To understand their cellular targeting, molecular docking of the same analogues was performed using the structure of P. falciparum Equilibrative Nucleoside Transporter 1 (PfENT1). This demonstrated that guanine, 8-azaguanine and 7-deazaguanine formed five hydrogen bonds each with the same amino acid residues of PfENT1, whereas 6-thioguanine’s orientation allowed only two hydrogen bonds with PfENT1. The binding pose of inosine was different from these nucleobases.DiscussionThese findings highlight the potential of guanine-based scaffolds, particularly 8-azaguanine and 7-deazaguanine, as promising leads for purine-based antimalarial drug development and the versatility of the PfENT1 transporter in the uptake of purine antimetabolites.